Current and Future Drug and Device Therapies for Pediatric Heart Failure Patients: Potential Lessons from Adult Trials - Bibhuti B. Das; William B. Moskowitz; Javed Butler (MDPI AG, 2021)
This review discusses the potential drug and device therapies for pediatric heart failure (HF) due to reduced systolic function. It is important to realize that most drugs that are used in pediatric HF are extrapolated from adult cardiology practices or consensus guidelines based on expert opinion rather than on evidence from controlled clinical trials. It is difficult to conclude whether the drugs that are well established in adult HF trials are also beneficial for children because of tremendous heterogeneity in the mechanism of HF in children and variations in the pharmacokinetics and pharmacodynamics of drugs from birth to adolescence. The lessons learned from adult trials can guide pediatric cardiologists to design clinical trials of the newer drugs that are in the pipeline to study their efficacy and safety in children with HF. This paper's focus is that the reader should specifically think through the pathophysiological mechanism of HF and the mode of action of drugs for the selection of appropriate pharmacotherapy. We review the drug and device trials in adults with HF to highlight the knowledge gap that exists in the pediatric HF population.